أثر الثقافة التنظيمية على الالتزام التنظيمي للعاملين دراسة حالة- شركة KEGT بالوادي - مريم, العابد; ابراهيم, عشيري; هاني, ناب (University of eloued جامعة الوادي, 2022)
"تعتبر الثقافة التنظيمية من بين أهم المتغيرات التي تم البحث فيها في السنوات الأخيرة، لما لها من أثر كبير على الكثير من المتغيرات الأخرى التي تحدد كم وكيف مخرجات المؤسسة . وتجد كثير من المنظمات الحديثة نفسها في حالة عجز عن رفع مستويات الالتزام لدى اعضائها ،من خلال تبني القيم والمعايير التي تنعكس في ثقافاتهم التي تناسب البيئة التي يعملون فيها ومن خلال مراجعة لبعض ادبيات الموضوع نجد ان متغير الثقافة التنظيمية هو الاكثر تواجدا وارتباطا مع متغير الالتزام التنظيمي في مختلف الابحاث والدراسات . فالثقافة التنظيمية تتطلب المعايير والقواعد التي تحدد كيف يتصرف الموظفون في مؤسستهم، فدورها مهم للغاية من اجل فهم السلوك التنظيمي، كما ان لها تاثير قوي على سلوك الموظفين ومواقفهم وهو ما يشير اليه على نحو ضمني الى افتراض العلاقة الترابطية بين المتغيرين ،وهو ما سنحاول الوقوف عليه في هذا المقال المتضمن لبعض جوانب الموضوع من خلال التطرق لاهم عناصر المتغيرين ( الثقافة التنظيمية ، الالتزام التنظيمي) ، وكذا محاولة شرح طبيعة العلاقة بينهما ""Organizational culture is one of the most important variables that have been researched in recentyears, because of itssignificant impact on manyother variables thatdetermine the outputs of the institution. . Many modern organizations find themselves in a state of inability to raise the levels of commitment of their members, by adopting the values and standards that are reflected in their cultures that suit the environment in which they work Through a review of some of the literature on the topic, we find that the organizational culture variable is the most present and associated with the organizational commitment variable in various research and studies, Their organization, itsroleisvery important in order to understand organizational behavior, and it has a strong influence on the behavior of employees and their attitudes, so managers and employees do not act in a vacuum; This is whatwewilltry to find out in this article, which includes some aspects of the topic, by addressing the most important elements of the two variables (organizational culture and organizational commitment), as well as trying to explain the nature of the relationship between them. "
ماستر ادارة اعمال
Keywords: ثقافة المنظمة، المؤسسة الاقتصادية، إدارة ثقافة المنظمة ، الالتزام التنظيمي; organizational culture- economic institution- management of organization culture - organiztional commitment